2006
DOI: 10.1017/s1355617706060206
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education and occupational complexity on rate of cognitive decline in Alzheimer's patients

Abstract: We explored the effect of education and occupational complexity on the rate of cognitive decline (as measured by the Mini-Mental State Examination) in 171 patients with a confirmed Alzheimer's disease (AD) diagnosis. Complexity was measured as substantive complexity of work and complexity of work with data, people, and things. Average lifetime occupational complexity was calculated based on years at each occupation. Participants were followed for an average of 2.5 years and 3.7 visits. In multivariate mixed-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
111
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 16 publications
14
111
0
5
Order By: Relevance
“…decline of cognitive functions once they are diagnosed with AD (Andel, Vigen, Mack, Clark, & Gatz, 2006;Hall et al, 2007;Roe, Xiong, Miller, & Morris, 2007;Scarmeas, Albert, Manly, & Stern, 2006;Stern, Albert, Tang, & Tsai, 1999;Wilson et al, 2004). This faster rate of decline is thought to be caused by a more advanced stage of neuropathology at diagnosis in AD patients with higher education, compared with patients with less education.…”
Section: Potential Confounding Effect Of Cases With Prodromal Admentioning
confidence: 99%
See 1 more Smart Citation
“…decline of cognitive functions once they are diagnosed with AD (Andel, Vigen, Mack, Clark, & Gatz, 2006;Hall et al, 2007;Roe, Xiong, Miller, & Morris, 2007;Scarmeas, Albert, Manly, & Stern, 2006;Stern, Albert, Tang, & Tsai, 1999;Wilson et al, 2004). This faster rate of decline is thought to be caused by a more advanced stage of neuropathology at diagnosis in AD patients with higher education, compared with patients with less education.…”
Section: Potential Confounding Effect Of Cases With Prodromal Admentioning
confidence: 99%
“…More important, when older individuals without dementia and AD patients are included in the same sample, effects of educational status may be leveled out because the current literature predicts that higher education causes cognitive decline over time to be slower in normal aging (e.g., Stern, 2002) but faster in AD (e.g., Andel et al, 2006). Although none of the individuals in the present study had a diagnosis of dementia at the time of testing, it is possible that individuals in a prodromal stage of a progressive neurodegenerative disease, such as AD, may have distorted the data.…”
Section: Potential Confounding Effect Of Cases With Prodromal Admentioning
confidence: 99%
“…Factors such as education (Stern et al, 1994), occupational status (Stern et al, 1995), life activities (Scarmeas et al, 2003), innate intelligence (Alexander et al, 1997), or a combination of these factors (Andel et al, 2006;Stern et al, 2005) are thought to compose aspects of cognitive reserve that help individuals acquire and use the set of skills necessary to cope with pathology and, therefore, perform normally on cognitive tasks. In this study, we chose to estimate cognitive reserve using a word-reading estimate of premorbid ability, namely the AMNART (Ryan & Paolo, 1992).…”
Section: Estimating Cognitive Reservementioning
confidence: 99%
“…Various proxy measures of cognitive reserve have been explored in several studies, including demographic based regression estimations (Barona et al, 1984), level of education, word reading estimates of premorbid IQ, and more recently, various combinations of education, occupation, and IQ (Andel et al, 2006;Stern et al, 1994Stern et al, , 1995Stern et al, , 2005. In this study, we chose to estimate cognitive reserve using the AMNART, in part because other studies found wordreading estimates of premorbid IQ more sensitive to the neurophysiological effects of AD than other demographic variables (Alexander et al, 1997) or a combination of variables (Bright et al, 2002).…”
Section: Dm Rentz Et Almentioning
confidence: 99%
“…De esta forma, una persona con alta reserva cognitiva soportará mayor cantidad de neuropatología disminuyendo el riesgo de manifestar los síntomas clínicos de la enfermedad (Andel, Vigen, Mack, Clark, & Gatz, 2006;De la Barrera, Donolo & Rinaudo, 2010). Desde un enfoque más pasivo de reserva, otros autores proponen el término de "reserva cerebral" que se basa en aspectos neurobiológicos relacionados con el tamaño cerebral, el número de neuronas o la densidad sinápti-ca.…”
Section: Introductionunclassified